Sistema braille en el aprendizaje de los estudiantes con capacidades visuales diferentes de la Universidad Técnica de Babahoyo Extensión Quevedo año 2019 - Uriarte Fajardo, Jurlendy Thayli (2020)
The Braille system is a tool by which people with different visual abilities communicate and acquire knowledge or message. This paper analyzes the importance of the use of the braille system in the students of the Technical University of Babahoyo, Quevedo extension. Doing the corresponding research determines the teaching process that the student with a different visual ability (blind) must have. In addition, the activities carried out and obtaining a better academic performance, in this project a case study was carried out with a university student with said visual impairment to know how to carry out the learning process. In the result obtained, it was determined that the student had to modify the tasks to the braille system to be able to perform them, because they are made for people with visibility, with the help of his grandmother, he manages the various activities. Including this, the corresponding interview was conducted to know in full how the student performed the exams, homework, and exhibitions. On the other hand, teachers have no knowledge of how to use this system, which is why they try to integrate the student, but it is still necessary for teachers to manipulate the Braille system. For Genesis (a blind student), it is important that teachers know how to make an ordinary Braille text, because it becomes impossible to modify the text. Given this, the student's grandmother usually modifies the text so that in this way she continues her specific learning. Given this issue, it is explained what the Braille system is and how it is used correctly, with this teachers can read and learn a technique that some universities and educational units of some cities in Spain have addressed, of which Madrid is.